Elaborating institutional arrangements to better enhance sustainable crop intensification in Uganda: a farmers’ perspective - Pali, P.N.; Tebeka, Y.A.; Schut, Marc; Mangheni, Margaret Najjingo; Wairegi, L.W.I.; Manyong, Victor; Asten, Piet J.A. van (Elsevier, 2023)
Weak and inefficient institutional arrangements have been identified as a major cause of the slow pace of agricultural growth in developing countries. Institutions – the humanly devised constraints that shape human interaction – play a significant role in Sustainable Crop Intensification (SCI) in Uganda. This study uses farmers' perceptions to assess institutions and their roles in SCI. We collected data from 135 rice and potato-producing households in Eastern and Southwestern regions of Uganda between January and February 2017. We used Focus Group Discussions to identify and categorize institutional typologies following which we asked households to evaluate several institutional aspects. Overall, institutional contributions to SCI were highly valued by farmers. Based on functional, organizational, and managerial obstacles, farmers perceived formal institutions to be ineffective while they perceived informal farmer's institutions to be the most relevant institutions as they provided financial resources that alleviated constraints to agricultural production and met livelihood needs. We found a lack of coordination between the micro, meso, and macro-level institutions, which then affected their institutional functionality to execute SCI. There is a need for innovation within existing institutions, and a status quo of institutional arrangements that would better respond to smallholders' needs.